PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MULTIMEDIA INTERAKTIF MENGGUNAKAN ADOBE FLASH CS6 UNTUK MATA PELAJARAN PADA PEKERJAAN DASAR OTOMOTIF KELAS X TBSM SMK NEGERI 1 LURAGUNG KUNINGAN: Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif Menggunakan Adobe Flash CS6 untuk Pekerjaan Dasar Otomotif - Rian Agustiana; Rabiman Rabiman; Setuju Setuju (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2022)
The purpose of this research is to produce learning media for automotive basic work in a way that is easy to operate and suitable for use in teaching and learning activities. This type of research is Research and Development with media development procedures through 10 stages of Sugiyono's adaptation. The data collection technique in this study is a validation sheet. The data analysis technique used quantitative analysis. The results of the media expert's validation show that the flash-based automotive basic work learning media is feasible with an average percentage of 80.5% assessment, covering three aspects of assessment, namely: media display aspects, aspects of using images, sound and evaluation questions, and aspects of the navigation system. The results of the material expert's validation showed that the flash-based automotive basic work learning media was very feasible with an average percentage of 89.2% assessment which included three aspects of assessment, namely: aspects of material relevance, aspects of learning material content, and aspects of ease of multimedia operation. The results of the user assessment indicate that the flash-based automotive basic work learning media is very feasible, with a percentage of 84.5% in small group trials and 90.30% in large group trials covering 5 aspects, namely: aspects of material relevance, aspects contents of learning materials, aspects of ease of operation, aspects of navigation menus, and aspects of system display design